Effect of Morus alba L. Ethanol Leaves Extract on Conjunctivitis Wistar Rats Model by Staphylococcus aureus - Gama Wisnu Sanjaya; Cicih Komariah; Dini Agustina (Journal of Agromedicine and Medical Sciences, 2021)
Conjunctivitis is inflammation in the conjunctiva, with clinical signs of exudation, cellular infiltration, and vascular dilatation. In adults, Staphylococcus species are the most common pathogenic bacteria resulting in bacterial conjunctivitis. Previous studies in vitro, explaining that mulberry leaf extract can inhibit the growth of S. aureus bacteria. The purpose of this study was to investigate the effect of mulberry leaf ethanol extract (Morus alba L.) on wistar mice conjunctivitis model by S. aureus. This type of research is true experimental with pretest-posttest control group design. The 24-wistar mice were adapted for 7 days. On day 8, a conjunctivitis induction was performed with 1.5 x 108 CFU / ml of S. aureus at 1 drop every 10 minutes for 1 hour (left 3 days) until conjunctivitis . On day 12 until day 19 (7 days), given mulberry leaf extract 45%, 55%, 65% and 75%. The results of TPC S. aureus logarithm on MSA medium of the 11th (pretest) day conjunctival swab and the 17th day (posttest) of rat adaptation were K (-) (5.70 and 4.07); K (+) (5.78 and 3.31); P1 (5.65 and 3.78); P2 (5.63 and 3.82); P3 (5.84 and 3.74); and P4 (5.69 and 3.63), with the posttest group there was improvement in conjunctivitis symptoms rather than the pretest group. The result of One Way Way Anova data analysis showed significant result at pretest p = 0,002 and posttest p = 0,046 (p <0,05) and paired t-test got significant result p = 0,000 (p <0,05). From this study it can be concluded that mulberry leaf extract (Morus alba L.) has the effect of decreasing the number of colonies of S. aureus bacteria and improving symptoms of conjunctivitis. Keywords: mulberry leaf extract, conjunctivitis, S. aureus